Strategic Restraint in Contests - Gil S. Epstein; Shmuel Nitzan (Center for Economic Studies and ifo Institute (CESifo), 2000)
Economic policy is modeled as the outcome of a (political) game between two inte rest groups. The possible ex-post (realized) outcomes in the game correspond to the proposed policies. In the literature the policies fought for are exogenous. We extend such games by allowing the endogenous determination of the proposed policies. In a first stage the groups decide which policy to lobby for and then, in a second stage, engage in a contest over the proposed policies. Our main result is that competition over endogenously determined policies induces strategic restraint that reduces polarization and, in turn, wasteful lobbying activities.
Keywords: 330; Interest groups; endogenous lobbying targets; voluntary restraint; polarization; voluntary restraint